2019
DOI: 10.1055/s-0039-1690728
|View full text |Cite
|
Sign up to set email alerts
|

POxAP Precatalysts and the Negishi Cross-Coupling Reaction

Abstract: Recently developed for the Fukuyama reaction, post-oxidative addition precatalysts (POxAPs) are also very efficient in catalyzing Negishi cross-coupling reactions between organohalides and organozinc reagents. Using very low catalyst loadings, POxAPs show similar catalytic activities to those of classical precatalysts such as XPhos Pd G4 or PEPPSI-IPr, with turnover numbers of up to 93,000. POxAPs are easily prepared, are stable to air and moisture, tolerate a wide range of functional groups in the Negishi cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In related research, bipyridines were synthesized using Negishi coupling as an alternative synthetic method. Tang et al reported particularly good results using PdBr(Ph)(PPh 3 ) 2 as a catalyst (Figure 3d) [36]. The catalyst, termed a post-oxidative addition precatalyst, can be easily prepared and is highly stable in air and in the presence of moisture.…”
Section: Negishi and Stille Coupling Reactions In Homogeneous Catalyt...mentioning
confidence: 99%
“…In related research, bipyridines were synthesized using Negishi coupling as an alternative synthetic method. Tang et al reported particularly good results using PdBr(Ph)(PPh 3 ) 2 as a catalyst (Figure 3d) [36]. The catalyst, termed a post-oxidative addition precatalyst, can be easily prepared and is highly stable in air and in the presence of moisture.…”
Section: Negishi and Stille Coupling Reactions In Homogeneous Catalyt...mentioning
confidence: 99%
“…In related research, bipyridines can also be synthesized by Negishi coupling as an alternative synthetic method reported by Bilhel. Particularly, good results are obtained when PdBr(Ph)(PPh3)2 is employed as a catalyst (Figure 3(d)) [36]. The catalyst, termed a post-oxidative addition precatalyst, can be easily prepared with high stability against air and moisture.…”
Section: Negishi and Stille Coupling Reactions In Homogeneous Catalyt...mentioning
confidence: 99%
“…Negishi cross-coupling of organozinc reagents with organohalides is a valuable reaction for a raft of applications, including total synthesis . The data gathered in this survey spanned 42 journal articles and 45 individual reactions. , The reaction data shows a preference for lower mol % values, particularly from papers published in the past decade. Interestingly, most ppm data points are distributed to lower ppm levels with more than 60% being below 500 ppm.…”
Section: Negishi Cross-couplingmentioning
confidence: 99%